2018
DOI: 10.1089/hs.2017.0052
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a Hypothetical Infectious Disease Outbreak on US Exports and Export-Based Jobs

Abstract: We estimated the impact on the US export economy of an illustrative infectious disease outbreak scenario in Southeast Asia that has 3 stages starting in 1 country and, if uncontained, spreads to 9 countries. We used 2014-2016 West Africa Ebola epidemic–related World Bank estimates of 3.3% and 16.1% reductions in gross domestic product (GDP). We also used US Department of Commerce job data to calculate export-related jobs at risk to any outbreak-related disruption in US exports. Assuming a direct correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Building on the present assessment of US export data, a related recent analysis of hypothetical outbreak scenarios in Southeast Asia suggested a substantial impact of outbreak disruptions on US exports and export-supporting jobs. 22 Combined with the present analysis, these analyses illustrate the potential economic disruption to the US export economy and our export-supporting jobs should a large-scale outbreak occur in any of the global health security priority countries. 22 These findings may be useful to inform decisions about the value of public health programs, investments, and policies aimed at building public health capacity worldwide.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Building on the present assessment of US export data, a related recent analysis of hypothetical outbreak scenarios in Southeast Asia suggested a substantial impact of outbreak disruptions on US exports and export-supporting jobs. 22 Combined with the present analysis, these analyses illustrate the potential economic disruption to the US export economy and our export-supporting jobs should a large-scale outbreak occur in any of the global health security priority countries. 22 These findings may be useful to inform decisions about the value of public health programs, investments, and policies aimed at building public health capacity worldwide.…”
Section: Discussionmentioning
confidence: 65%
“… 22 Combined with the present analysis, these analyses illustrate the potential economic disruption to the US export economy and our export-supporting jobs should a large-scale outbreak occur in any of the global health security priority countries. 22 These findings may be useful to inform decisions about the value of public health programs, investments, and policies aimed at building public health capacity worldwide. When all countries are able to rapidly prevent, detect, and control outbreaks at their source, the risk of large outbreaks and pandemics can be reduced and global health security enhanced.…”
Section: Discussionmentioning
confidence: 65%
“…Because the countries affected by the 2014 West Africa Ebola outbreak are relatively minor trading partners for the United States, it is plausible that epidemics affecting larger partner countries would be more consequential. For example, the East Asia and Pacific region is one area with key U.S. trade relationships that has an elevated risk of emerging epidemics, where Indonesia alone is both a top destination for U.S. exports (Office of the U.S. Trade Representative, 2018) and an identified hotspot for potential infectious outbreaks (Perkins, Patrick, Patel, & Fenwick, 2007) and where hypothetical outbreak scenarios have suggested that billions in U.S. exports could be at stake in the event of an infectious disease epidemic (Bambery et al, 2018). The expected worldwide economic loss from a major influenza pandemic has been estimated at 0.6% of global income (Fan, Jamison, & Summers, 2017), with country-specific pandemic simulations predicting losses of up to 6% of GDP for several Western European countries (Keogh-Brown, Smith, Edmunds, & Beutels, 2010) and up to 7.3% of GDP for Australia (Verikios, McCaw, McVernon, & Harris, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, T c -T w > 0. We extracted the gross domestic product (GDP) due to Ebola epidemic per week, and fixed the cost, c , as 14 million United States dollars (USD) per week ( Bambery et al, 2018 ). Second, let Pr ( T c ) and Pr ( T w ) as the probability of observing at least one additional case given the waiting time T c and T w .…”
Section: Cost-effectiveness Analysismentioning
confidence: 99%